2011
DOI: 10.1590/s2237-93632011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between location, size and histologic type of colorectal polyps at the presence of dysplasia and adenocarcinoma

Abstract: Adenocarcinoma represents 96-98% of colorectal neoplasms, and neoplastic polyps (adenomas) are their precursors. The aim of this study is to correlate size, location and histologic type of colorectal polyps at the presence of dysplasia and adenocarcinoma. Methods: Colonoscopies from January/2007 to December/2008 were retrospectively studied, in order to evaluate the characteristics of the polyps. Results and Discussion: Out of the 2,401 analyzed colonoscopies, 583 (24.3%) presented polyps. Due to the lack of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Our mouse model is limited to the precarcinoma stage. However, even at this stage, the size of adenomas strongly correlates with the grade dysplasia; large adenomas usually display high‐grade dysplasia, and vice versa , smaller in size adenomas exhibit lower grade of dysplasia [ ]. Since adding gamma‐cyclodextrin and propolis to control or Western diets decreased the number of large (>10 mm 2 ) adenomas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our mouse model is limited to the precarcinoma stage. However, even at this stage, the size of adenomas strongly correlates with the grade dysplasia; large adenomas usually display high‐grade dysplasia, and vice versa , smaller in size adenomas exhibit lower grade of dysplasia [ ]. Since adding gamma‐cyclodextrin and propolis to control or Western diets decreased the number of large (>10 mm 2 ) adenomas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been showed that approximately two-third of patients had solitary polyps, and advanced age is associated with detecting larger polyps (Lowenfels et al, 2011;Silva et al, 2014;Solakoğlu et al, 2014) Of the 1,106 polyps, adenomatous polyps were the most prevalent types, followed by mucosal tags/polyps, hyperplastic and serrated polyps, inflammatory polyps, hamartomatous, and malignant lesions. Frequency of adenomatous polyps in selected Iranian studies ranged between 61% and 90% (Mirzaie et al, 2012;Darvish et al, 2013;Iravani et al, 2014;Delavari et al, 2014;Hajmanoochehri et al, 2014;Geramizadeh and Keshtkar-Jahromi, 2013), and in some other countries varies between 41% and 61% (Zhou et al, 2017;Kefeli et al, 2014;Wickramasinghe et al, 2014;Valarini et al, 2011). It seems that in some of the mentioned studies in Iran, due to over-diagnosis of non-neoplastic polyps under Most polyps, including adenomas, located in the left colon, especially rectosigmoid.…”
Section: Discussionmentioning
confidence: 99%
“…In Iranian studies, this group accounts for 0.3% to 2.1% of all polyps (Mirzaie et al, 2012;Iravani et al, 2014;Delavari et al, 2014;Hajmanoochehri et al, 2014;Geramizadeh and Keshtkar-Jahromi, 2013), and in other countries, this group constitutes 2% to 17% of all colonic polyps (Zhou et al, 2017;Kefeli et al, 2014;Wickramasinghe et al, 2014;Valarini et al, 2011). It seems that either these types of colonic polyps in Iran are not as common as western countries, or they remain undetected and misclassified as other polyps especially hyperplastic ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations